2021
DOI: 10.1101/2021.04.09.21255047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicenter evaluation of a fully automated high-throughput SARS-CoV-2 antigen immunoassay

Abstract: Background: Molecular testing for SARS-CoV-2 continues to suffer from delays and shortages. Antigen tests have recently emerged as a viable alternative to detect patients with high viral loads, associated with elevated risk of transmission. While rapid lateral flow tests greatly improved accessibility of SARS-CoV-2 detection in critical areas, their manual nature limits scalability and suitability for large-scale testing schemes. The Elecsys® SARS-CoV-2 Antigen assay allows antigen immunoassays to be carried o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…At the end of the data extraction process, 37 studies were still in preprint form [4,171,173,174,177,180,190,192,201,204,205,207,211,[214][215][216]218,220,222,223,225,227,231,233,234,238,240,244,247,253,257,265,267,284,287,290,293]. All studies were written in English, except for 2 in Spanish [175,280].…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…At the end of the data extraction process, 37 studies were still in preprint form [4,171,173,174,177,180,190,192,201,204,205,207,211,[214][215][216]218,220,222,223,225,227,231,233,234,238,240,244,247,253,257,265,267,284,287,290,293]. All studies were written in English, except for 2 in Spanish [175,280].…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…At the end of the data extraction process, 37 studies were still in preprint form [4,171,173,174,177,180,190,192,201,204,205,207,211,214216,218,220,222,223,225,227,231,233,234,238,240,244,247,253,257,265,267,284,287,290,293]. All studies were written in English, except for two in Spanish [175, 280].…”
Section: Resultsmentioning
confidence: 99%
“…still performed favorably (overall sensitivity 74.7%, total 1787 samples and 16.7% RT-PCR positivity) compared with other automated antigen assays where reported sensitivities ranged from 41.2% to 65.9%26,[28][29][30] overall, although all still falling short of the 80% sensitivity WHO recommendation 11. In a world without resource constraints, RT-PCR would be the test of choice for every testing situation, however, as resource availability is unequal, there is a…”
mentioning
confidence: 86%
“…A recent study has suggested that antigen assays performed on high throughput immunoanalysers may offer a viable solution for patient screening, or in situations where RT-PCR testing is not readily available. 26 In this present study, we evaluated the performance of the au- handling error, rather than loss of assay sensitivity for the mutant antigen as 21/22 such mutants were correctly detected (Figure 2).…”
Section: Positive Predictive Value (Ppv) and Negative Predictive Valu...mentioning
confidence: 99%
See 1 more Smart Citation